Role Exchange in Student-led Simulation: The Importance of Nursing Students Taking the Role of Patients - Anneline Røssland RN, MNSc; Alette Svellingen RN, MNSc, PhD; Kari Røykenes RN, MSc, PhD (SAGE Publishing, 2022)
Introduction As simulated patients in simulation-based learning, nursing students can contribute to a better understanding of the patient perspective in clinical practice. Objective The aim was to explore final-year nursing students' experiences in roleplaying as patients in a student-led simulation of difficult conversations as a form of preparing for practice in mental healthcare and homecare nursing. Methods The study was conducted using a qualitative research design. After the student-led simulation, four of the students participated in multistage focus group interviews over a period of six months: the first interview was immediately after simulation and the second was after clinical practice. Findings One main theme was identified before clinical practice: "simulating the patient contributes to preparation for difficult conversations in practice." Two main themes were identified after the students' clinical practice: "simulation of both the nurse and patient lays the foundation for communicating with patients" and "the value of silence." Conclusion The findings indicate that simulation training and role exchange when students roleplay both as the patient and nurse contribute to a greater understanding of the patient perspective, and students benefit from this when communicating with patients in clinical practice.